Brazilin blocks catabolic processes in human osteoarthritic chondrocytes via inhibition of NFKB1/p50. Issue 9 (8th May 2018) - Weinmann, Daniela; Mueller, Monika; Walzer, Sonja M.; Hobusch, Gerhard M.; Lass, Richard; Gahleitner, Claudia; Viernstein, Helmut; Windhager, Reinhard; Toegel, Stefan
ABSTRACT: This study aimed to evaluate the chondroprotective and anti‐inflammatory activity of brazilin in human osteoarthritic (OA) cartilage and chondrocytes with particular focus on the nuclear factor‐kappa B (NF‐κB) pathway. Therefore, brazilin was isolated from Caesalpinia sappan and identified using high performance liquid chromatography (HPLC). The effect of brazilin was assessed in cartilage explants treated with 10 ng/ml interleukin (IL)‐1β and 10 ng/ml tumor necrosis factor (TNF)‐α using histological and biochemical glycosaminoglycan (GAG) analyses and in primary chondrocytes treated with 10 ng/ml IL‐1β using RT‐qPCR, ELISA, and Western blot. The involvement of NF‐κB signaling was examined using a human NF‐κB signaling array and in silico pathway analysis. Brazilin was found to reduce the GAG loss from cartilage explants stimulated with IL‐1β and TNF‐α. NF‐κB pathway analysis in chondrocytes revealed NFKB1/p50 as a central player regulating the anti‐inflammatory activities of brazilin. Brazilin suppressed the IL‐1β‐mediated up‐regulation of OA markers and the induction of NFKB1/p50 in chondrocytes. In conclusion, brazilin effectively attenuates catabolic processes in human OA cartilage and chondrocytes—at least in part due to the inhibition of NFKB1/p50—which indicates a chondroprotective potential of brazilin in OA. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2431–2438, 2018.